2022
DOI: 10.1177/17579139221081400
|View full text |Cite
|
Sign up to set email alerts
|

Group singing for health and wellbeing in the Republic of Ireland: the first national map

Abstract: Aims: (1) To catalogue and map all singing for health and wellbeing groups in the Republic of Ireland (ROI); (2) determine how they prioritise health outcomes; (3) understand what they consider success; and (4) identify gaps in provision. Methods: A novel mixed-methods survey was distributed electronically through SING Ireland (the Choir Association of Ireland), artsandhealth.ie, and to 2736 potential stakeholders with links to singing for health and wellbeing and singing on social prescription (SSP) from Octo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…For SP interventions that are more intensive, LW assistance is more targeted and prolonged to support the individual's health priorities, for example, obesity, depression and decreased physical activity (Morse et al., 2022). Referrals from LW to community‐based organizations vary in terms of environment and content and range from ecotherapy (Thomas et al., 2020), art therapy (Stickley & Eades, 2013), music therapy (Helitzer & Moss, 2022), employment and housing support (Chatterjee et al., 2017) and interventions to address social isolation (Liebmann et al., 2022). Social prescribing is used globally (Global Social Prescribing Alliance, 2021; Morse et al., 2022), but is more established within the United Kingdom (Chatterjee et al., 2017; Mercer et al., 2019) and North America (Kangovi et al., 2018; Ramirez et al., 2020) compared to other regions (Morse et al., 2022).…”
Section: Social Prescribingmentioning
confidence: 99%
“…For SP interventions that are more intensive, LW assistance is more targeted and prolonged to support the individual's health priorities, for example, obesity, depression and decreased physical activity (Morse et al., 2022). Referrals from LW to community‐based organizations vary in terms of environment and content and range from ecotherapy (Thomas et al., 2020), art therapy (Stickley & Eades, 2013), music therapy (Helitzer & Moss, 2022), employment and housing support (Chatterjee et al., 2017) and interventions to address social isolation (Liebmann et al., 2022). Social prescribing is used globally (Global Social Prescribing Alliance, 2021; Morse et al., 2022), but is more established within the United Kingdom (Chatterjee et al., 2017; Mercer et al., 2019) and North America (Kangovi et al., 2018; Ramirez et al., 2020) compared to other regions (Morse et al., 2022).…”
Section: Social Prescribingmentioning
confidence: 99%
“…However, the implementation of music therapy as a social prescription faces challenges such as the formalization of the social prescribing process, securing buy-ins from healthcare professionals, sustainable funding, and institutional knowledge retention [18]. One review identified several barriers to the broader integration of singing on prescription, including the lack of formalization in the social prescribing process, challenges in securing support from general practitioners and healthcare professionals, difficulties in sustaining funding, and organizational changes leading to staff turnover and the loss of institutional knowledge [19].…”
Section: Introductionmentioning
confidence: 99%